Fermentation Versus Meat Preservatives to Extend the Shelf Life of Mealworm (Tenebrio molitor) Paste for Feed and Food Applications - Borremans, An; Smets, Ruben; Van Campenhout, Leen (Frontiers in Microbiology, 2020)
Freshly prepared pastes from blanched mealworms (Tenebrio molitor) are highly perishable and prone to microbial and chemical changes upon storage due to their high water activity, near–neutral pH and their rich nutrient profile. Their shelf life is short unless preservation methods are used. In this study, the effects of preservatives (sodium nitrite and sodium lactate) and lactic acid fermentation (with the starter cultures Bactoferm® F-LC and Lactobacillus farciminis) on the microbiological and the chemical stability of mealworm pastes stored at 4°C were compared. During the storage experiment, the pH, water activity, colour, microbial counts and fat oxidation were monitored. In addition, the prevalence of the pathogens Bacillus cereus, Salmonella spp., and Listeria monocytogenes were studied. Microbial quality evaluation of the mealworm pastes showed that the addition of preservatives did not inhibit microbial growth during refrigerated storage, reaching the upper limits for consumption between seven and 14 days. By contrast, the acid medium (pH < 4.50) created by fermentation stabilized all microbial populations investigated, indicating that these pastes could be consumed up to (at least) 8 weeks of refrigerated storage. Listeria monocytogenes, Salmonella and Bacillus cereus were not detected in any of the samples and lipid oxidation of the samples was minimal. Altogether, this study shows that lactic fermentation can be used successfully to inhibit microbial growth, to maintain chemical quality, and to extend the shelf life of mealworm pastes stored at 4°C.